PENGARUH PEMBERIAN EKSTRAK BIJI KOPI ROBUSTA (Coffea canephora) LAMPUNG TERHADAP JUMLAH SEL PURKINJE CEREBELLUM TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR Sprague dawley YANG DIINDUKSI MONOSODIUM GLUTAMAT - Ilham Nugroho; Anggraeni Janar Wulan; TA Larasati; Khairun Nisa Berawi (Majority, 2023)
Excessive consumption of monosodium glutamate has a neurotoxic effect on the brain, one of which is the cerebellum. The caffeine and chlorogenic acid compounds contained in coffee beans have potential as an anti-inflammatory and neuroprotective agent thus protecting rats from neurotoxicity by glutamate involved with the death of cerebellar purkinje cells. This research is an experimental study with Completely Randomized Design (CRD) with a Posttest Only Control Group Design approach. The research subjects were 25 rats which were divided into 5 groups which are K- (aquadest 3,5 ml/day), K+ (MSG 4 g/kgBW/day), P1, P2, P3 (MSG 4 g/kgBW/day and robusta coffee extract lampung 1,5 ml/200gBW/day with a concentration of 0,03 g/ml; 0,06 g/ml; 0,12 g/ml respectively) with each group consisting of 5 rats. The number of purkinje cells is calculated by manual counting assisted by Image J software in 3 sections with 5 visual fields each in 400x magnification. The average number of cerebellar purkinje cells in K-, K+, P1, P2, and P3 were 22,72; 11,88; 22,44; 25,28; 27,12 respectively. One Way ANOVA test obtained p value=0,000 (p<0,05). Post Hoc LSD test on the number of purkinje cells showed a significant differences (p<0,05) between K- and K+ (p=0,000), K- and P3 (p=0,006), K+ and P1 (p=0,000), K+ and P2 (p=0,000), K+ and P3 (p=0,000), and P1 and P3 (p=0,004). There is an effect of robusta coffee extract (Coffea canephora) lampung againsts to the number of cerebellar purkinje cells in male rats strain (Rattus norvegicus) Sprague dawley induced by monosodium glutamate.